Analysis of Coupling Characteristic of the Planetary Multi-stage Gear Transmission System - Wang Xin; Li Yousheng (Jixie chuandong)
In order to study the coupling vibration mechanism of the planetary multi-stage gear transmission system,the dimensionless dynamics equations of the planetary multi-stage gear transmission system which contains a two-stage fixed-axis gear and a one-stage planetary gear are established. Contrasted the bifurcation characteristics of the two-stage fixed-axis gear,the planetary gear transmission system and the planetary multi-stage gear transmission system to study the nonlinear coupling characteristics of the multi-stage gear system. The results show that the crisis points of the 1st fixed-axis gear reduce due to coupling effects which increases the stability of the system. At the same time,the chaotic motion of the planetary gear is transferred to the fixed-axis gear,it causes a big range of chaotic motion on the 2nd fixed-axis gear and reduces the stability of the system.